ROBLEMATIKA PERLINDUNGAN PEREMPUAN KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DI INDONESIA PERSPEKTIF HUKUM ISLAM - Lukman Santoso; Bustanul AriÂin (LPPM STAI DARUSSALAM LAMPUNG, 2013)
The case of household violence physically or psychologically nowadays isoften we hear. That reality factually shows that the violence in the householdtoward wife, is the common phenomenon in the societal environment.This case is sure not away from the social construct which is developed inthe middle of society that s husband is the head of family and has a fullauthority to the part of family including wife. In that context this researchis making effort to peel off how the problem of protecting implementationtoward women in violence (KDRT) and Islam gives the answers.In the context of women protection in the household, Al-Quran texts give alot of answers which order to make the relationship of household as maâ€™rufin the meaning of equal, fair, and democratic. In the terminology of UshulFiqh, this concerning agrees with what the goals of law are, that is the lawtoward Âive aspects (al-kulliyat al-khams), which one is soul protection (hifzan-nafs). This explains that Islamic law brings the mission of protection, itis as a Godâ€™s mercy to all humans in this world. It is also harmonization withthe law of women protecting in Indonesia.